COVID-19, firm innovation strategy and production efficiency: A stochastic frontier analysis of Caribbean firms - Preeya Mohan; Eric Strobl (Inter-American Development Bank (IDB), 2023)
While Caribbean Small Island Developing States (SIDS) have been exposed to frequent external shocks in the past, the Coronavirus disease of 2019 (COVID-19) pandemic is like no other, representing the largest economic shock experienced globally in decades. The objective of this paper is to contribute to a better understanding of the innovation strategy and production efficiency of Caribbean firms during COVID-19. More specifically, it adopted a Stochastic Frontier Analysis (SFA) to investigate COVID-19, innovation, and technical efficiency for 13 Caribbean countries using the Innovation, Firm Performance, and Gender (IFPG) firm-level dataset. The results indicate that firms expect average technical efficiency to fall by over 100 percent because of COVID-19. Pre-COVID-19, 39 percent of firms implemented general innovations (product, process, organizational, and marketing) over the past three years, and 50 percent green innovations (environmental improvements), while the pandemic negatively affected 42 percent of these innovations. Firms that carried out general innovations experienced a positive effect on technical efficiency, while green innovations had a negative effect. During COVID-19 only 12 percent of firms initiated general innovations and 17 percent green innovations. These general innovations improved technical efficiency, while innovations that were affected by COVID-19 had a negative effect, and green innovations did not necessarily have a positive effect.
Keywords: D22; D24; O32; Q55; 330; innovation; green innovation; COVID-19; production function; technical efficiency; stochastic frontier analysis; small islanddeveloping states